A Pariah people the anthropology of Antisemitism - Maccoby, Hyam 1924-2004 (Constable, 1996)
The author offers and anthropological explanation for the phenomenon. in making use of anthropological analysis this book provides an explanation of the failure of apparently promising strategies for Normalising the status of Jews.
Keywords: Bibel -- Neues Testament; Antisemitisme; Antisémitisme; Christianisme et antisémitisme; Antisemitismus; Geschichte; Antisemitism -- History; Christianity and antisemitism; Anthropologie; Christentum; Antijudaismus